Surface Microbiology of Smartphone Screen Among the Nursing Staffs Working in Intensive Care Unit (ICU) Of Tertiary Care Hospital - Shinde, Aishwarya J; Soumya S; Najeeb, Mohd. Aadam Bin; Jangid, Sunil (National Journal of Medical Research, 2025)
Background: The increasing use of mobile phones by healthcare professionals in intensive care units (ICUs) has raised concerns about their potential role as reservoirs for pathogenic microorganisms, contributing to healthcare-associated infections (HAIs). This study investigates the extent of microbial contamination on smartphones used by nursing staff in critical care, highlighting the need for enhanced infection prevention strategies. Methods: Smartphones used by ICU nursing staff were swabbed and analyzed microbiologically. Samples were cultured on MacConkey and blood agar, followed by Gram staining and biochemical identification per CLSI guidelines, to detect and identify potential pathogens in a high-risk clinical setting. Results: Out of 129 mobile phones analyzed, 64.3% showed pathogenic growth. Monomicrobial growth was found in 95.1% of cases, and polymicrobial in 4.8%. Gram-positive cocci dominated (82.7%), mainly Staphylococcus aureus (68%). Gram-negative bacilli (17.2%) included E. coli (40%), K. pneumoniae (26%), P. aeruginosa (20%), and A. baumannii (13%), indicating significant contamination. Conclusion: Mobile phones used by healthcare workers can carry harmful pathogens, increasing the risk of HAIs. Regular disinfection, staff education, and clear phone usage policies are essential to reduce contamination, enhance infection control, and promote a safer clinical environment.